Reactivating elements chemistry, ecology, practice - Papadopoulos, Dimitris; Puig de la Bellacasa, María 1972-; Myers, Natasha 1974- (Duke University Press, 2021)
The contributors to Reactiving Elements explore how studying elements--as the foundations of the physical and social world--provide a way to imagine alternatives to worldwide environmental destruction
Keywords: Ökologische Chemie; Chemische Ökologie; Ecocriticism; Chemical ecology; Ecology; Environmental chemistry